(untitled) (Crimson Journal of Science and Technology, 2025)
Introduction: Diabetes mellitus is a chronic metabolic disease that is manageable by proper adherence to anti diabetic medications, resulting in glycemic control, complications prevention and a better prognosis of the patients. The aim of the study was to find out the medication adherence among diabetic patients in a hospital, Rupandehi. Methods: A Hospital-based descriptive cross-sectional study was conducted to find out medication adherence among 313 diabetic patients selected through a non-probability purposive sampling method. Data was collected by using a semi-structured interview schedule and was analyzed by using descriptive statistics (frequency and percentage) and inferential statistics (chi-square) with Statistical Package for Social Sciences software (SPSS) version 20.0. The total duration of the study was from March 1, 2024 to September 1, 2024. Results: The findings of the study showed that 38.3% of the diabetic patients were adherent to anti-diabetic medications. There is a statistically significant association between the level of medication adherence with co-morbidity conditions (p=0.024) and medication expenses (p=0.013). Conclusions: Based on the study findings, it is concluded that less than half of the respondents were adherent to anti-diabetic medications. It is recommended that nurses and doctors working in the medicine department conduct an awareness program, including counseling sessions regarding diabetes mellitus, the importance of adherence to anti-diabetic medications and participation in the government health insurance program to reduce medication expenses.